HAND GRIP STRENGTH AS A MODALITY FOR SARCOPENIA IN PATIENTS WITH CHRONIC LIVER DISEASES - Haider, Iqbal; Atta Ullah; Laila Hassan; Maaz Ullah; Abdul Majid (Journal of Postgraduate Medical Institute, 2023)
ABSTRACT Objective: To determine the frequency of normal and abnormal handgrip strength in patients with chronic liver disease. Methodology: This descriptive cross-sectional study has been conducted in the Department of Medicine Khyber Teaching Hospital in Peshawar, Pakistan. Data was collected over six months, from October 2020 to April 2021 after the approval by the institutional ethical board. Each participant gave informed consent before being included in the study. A total of 254 patients were included. Every patient was asked to hold the Hand Dynamometer in the dominant hand as per the set criteria. Three readings were taken with a resting period of ten seconds between each, and the highest reading in kilograms was considered final. Calliper (Lange®) was used to measure the thickness of the Triceps skin fold (TSF) and Adductor pollicis muscle (APMT). The anthropometric value of TSF and abdominal circumference (AC) was taken, and measurements were also made of the mid-arm muscle circumference (MAMC). Results: Among 254 patients, the mean age was 48 ± 10.59 years while145 (57%) patients were male, while 109 (43%) were female. Moreover, 125 (49%) patients had normal handgrip strength (HGS), while 129 (51%) had abnormal handgrip strength. The mean APMT was 16.5 ± 3.4 mm, the mean MAMC 24.2 ± 3.7 cm, and the mean TSF was 15 ± 13.11 mm. Conclusion: Abnormal handgrip strength was reported in more than half of patients with chronic liver disease. HGS test is a convenient and cost-effective bedside tool to determine sarcopenia in chronic liver disease patients.